Exploratory factor analytical study of depressive symptomatology: An Arab experience with a sample comprising college students, using the revised Beck Depression Inventory - Al-Turkait, Fawziyah A. (Ann Saudi Med, 2012)
BACKGROUND AND OBJECTIVES: An understanding of the domains of depressive symptomatology could facilitate valid and interpretable comparisons across cultures. The objective of the present study was to assess the factor structure of the Beck Depression Inventory-II (BDI-II) in an Arab sample comprising college students, in comparison to the international data. DESIGN AND SETTING: Cross-sectional questionnaire survey of Arab college students in their classrooms over a 1-year period. PATIENTS AND METHODS: Participants (n=624) who completed the questionnaire, which had been translated into Arabic, during the 2007–2008 academic session. Exploratory factor analysis was done by principal axis factoring with oblique rotation. RESULTS: Factor 1 consisted of psychological symptoms. Factor 2 mainly comprised somatic symptoms, but with some affective symptoms (loss of interest, irritability). Factor 3 also belonged to a purely psychological domain, whereas factor 4 was another mixture of somatic and psychological symptoms (41.8% of variance explained). Thus the four domains were as follows: cognitive I, somatic-affective I, cognitive II, and somatic-affective II. These domains were similar in construct to the original subscales on which the BDI-II was validated for students in North America. Our four-factor solution fulfilled the recommended criteria, namely, a strong first factor, simple structure (parsimony), and stable factors with construct meanings that are in line with theory. CONCLUSION: Our factor structure defined depression in a manner consistent with theory, in that sadness, self-dislike, and guilt feelings defined the cognitive domain. whereas irritability and changes in sleep pattern and appetite mostly defined the somatic-affective domain. The BDI-II has construct validity across cultures.